Beyond Linguistics: Exploring the Cognitive and Motivational Barriers to Essay Writing for Tertiary Students - Anaktototy, Karolis; Sekewael, Mansye; Latief, Muhammad Ridha Anugrah; Bin-Hady, Wagdi Rashad Ali (Universitas Negeri Makassar, 2023)
In higher education, developing strong writing skills is crucial for students' academic and career success. Unfortunately, this important aspect of education has been somewhat neglected in the context of Maluku province. Therefore, this study, serves the crucial purpose of shedding light on the multifaceted factors that underpin the deficiencies in writing skills. The primary aim of this study is to explore the fundamental factors contributing to the deficiencies in tertiary students' writing skills. To accomplish this, we conducted a quantitative survey, selecting a random sample of 70 Moluccan local students out of 120 who were enrolled in an essay writing class. Results indicate that cognitive factors play the most pivotal role in contributing to deficiencies in writing skills, boasting a remarkably high path coefficient value of 0.846. Linguistic factors and motivational aspects closely follow, with values of 0.556 and 0.528, respectively. The deficiency in writing skills among students can be attributed to a lack of internal motivation for learning, and inadequate opportunities provided by teachers for real-life observation and learning. For effective improvement in writing abilities, students need both an intrinsic motivation to learn and consistent guidance and stimulation from educators. The process of writing not only involves linguistic capability but also a deep cognitive understanding, emphasizing the need for students to process and present their thoughts comprehensively and appealingly. Improving tertiary students' writing skills require a comprehensive approach that addresses cognitive, linguistic, and motivational factors. Implementing these implications can result in more effective teaching methods and improved writing outcomes for students.